2007
DOI: 10.1111/j.1749-4877.2007.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and management of rodents in no‐till agriculture in Washington, USA

Abstract: No-till farming is an important approach to sustainable agriculture because it can conserve soil and water resources. Unfortunately, rodent populations can thrive under no-till conditions because burrow systems are not disrupted by annual plowing and plant residues build-up on the surface, providing cover and insulation. This can result in substantial crop damage. We assessed rodent populations, habitat use, food habits, and crop damage in a no-till cropping system in Washington, USA. We also conducted prelimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
(20 reference statements)
0
28
0
1
Order By: Relevance
“…Previous studies on roof rats have found that elevated baits are typically more effective than bait placed at ground level (e.g., Campbell et al 1998), while bait is typically broadcast on the ground for deer mouse control (e.g., Witmer et al 2007b). As such, we were not sure how deer mice would respond to elevated bait stations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on roof rats have found that elevated baits are typically more effective than bait placed at ground level (e.g., Campbell et al 1998), while bait is typically broadcast on the ground for deer mouse control (e.g., Witmer et al 2007b). As such, we were not sure how deer mice would respond to elevated bait stations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, most species of voles exhibit strong population cycles, whereby they reach very high densities (>2471/ha) every 3À5 years. Severe damage to agricultural and forestry resources occurs at these peak densities (Witmer & VerCauteren 2001;Witmer et al 2007;Witmer & Proulx 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In open settings such as croplands or orchards, the task is much more difficult and the chance of success is small. Although research in this area continues, there are few successes to report at this time (Pelz 2003;Witmer et al 2007cWitmer et al , 2008b). …”
Section: Barriers and Exclusionmentioning
confidence: 99%
“…Many of these manipulations are not done just to reduce rodent habitat (which may be an incidental benefit) but for other reasons such as to reduce vegetative competition with crops or trees, to reduce soil pathogens, or to prepare sites for planting. Burning, plowing, disking, herbicide application all reduce vegetative cover, at least for the short term, and usually greatly reduce rodent populations Witmer et al 2007c). Plowing and disking have the additional advantage of disrupting the burrows of rodents (Salmon et al 1987).…”
Section: Habitat Managementmentioning
confidence: 99%
See 1 more Smart Citation